الأوضاع السياسية لجورجيا في ضوء "حولية كارتلي" الكرجية لمؤرخ مجهول "1027-1060 م." - عبدالباسط، عفاف عبدالراضي (الإتحاد العام للآثاريين العرب, 2024)
مثل القرن الحادي عشر الميلادي/ الخامس الهجري مرحلة حاسمة في تاريخ جورجيا، إذ كان على خلفاء الملك باجراط الثالث Bagrat III (٩٧٥ -۱٠١٤م) مواصلة جهوده لإتمام الوحدة السياسية لمملكة الكرج، لكنهم اصطدموا بطموح الأمراء الكرج المحليين وأطماع البيزنطيين في بلادهم، في الوقت الذي بدأ فيه السلاجقة يبحثون عن موطأ قدم في القوقاز. وسوف يناقش البحث أهم الظروف السياسية التي مرت بها جورجيا على الصعيدين الداخلي والخارجي بدءًا من عام ١٠٢٧م، وهو العام الذي تولى فيه الملك باجراط الرابع Bagrat IV (1027-2072م) حكم مملكة الكرج حتى عام ١٠٦٠م الذي شهد نجاحه في التغلب على ألد خصومه الأمير الإقطاعي ليباريت الرابع Liparit IV رجل بيزنطة الأول في القوقاز في تلك المرحلة؛ وذلك من خلال "حولية كارتلي" الكرجية لمؤرخ مجهول. The eleventh century A.D. / fifth century A.H. represented a decisive stage in the history of Georgia, as the successors of King Bagrat III (975- 1014 A.D.) had to continue his efforts to complete the political unity of the Kingdom of Georgia, but they collided with the ambitions of the local Georgian princes and the colonial aspirations of the Byzantines in their country at a time when Seljuks began to seek a foothold in the Caucasus. The research will discuss the most important political conditions that Georgia went through, both domestically and internationally, from the year 1027 A.D., when King Bagrat IV (1027–1072) assumed control of the Kingdom of Georgia, until the year 1060 A.D., which witnessed his success in overcoming his staunchest opponent, the feudal prince Liparit IV, the main man of Byzantium in the Caucasus at that stage, through the Georgian Chronicle, "The Chronicle of Kartli," written by an anonymous historian.
Keywords: الدولة البيزنطية -- مملكة جورجيا -- التاريخ السياسي